Laryngeal Chondrosarcoma as a Rare Cause of Subglottic Stenosis - Kerem Kökoğlu; Özlem Canöz; Serap Doğan; Emrah Gülmez; İmdat Yüce; Sedat Çağlı (Case Reports in Otolaryngology)
Laryngeal chondrosarcoma (CS) is a very rare entity. It is usually seen in 50–80-year olds. It is developed from cricoid cartilage largely. Patients have laryngeal CS complaint of respiratuvar distress, dysphonia, and dysphagia generally. A submucous mass is usually seen in physical examination with an intact mucosa. Distant metastasis is rare in CSs. Main treatment is surgical excision. An 82-year-old patient who has respiratuvar distress is presented in this paper and laryngeal CS is reviewed in the light of the literature.